Convenient connection technology data model supporting optimized information exchange between CAx-systems. Issue 5 (3rd September 2018) - Kreis, Alexander; Hirz, Mario; Stadler, Severin; Salchner, Markus; Rossbacher, Patrick
ABSTRACT: In the automotive industry, the number of multi-material bodies is increasing steadily. The background for this rise is, that the body weight can be reduced due to a mix of different materials, by almost the same material costs. This technology requires a high number of different kinds of connection types, which requires the implementation of a high amount of meta data. This large date volume plays a crucial role in the development process, especially in terms of the applied CAx-environment. A big issue is the data exchange between the different areas design, analyses and manufacturing. By optimizing the data exchange process, data quality can be improved and data quantity can be reduced. The present paper focusses on an approach of a new data model, which deals with data processing and storage, in an attempt, to further reduce the effort of data management and costs. GRAPHICAL ABSTRACT: